Research for city practice. Issue 1 (2nd January 2020) - Grant, Marcus; McCunn, Lindsay; Ahmad, Sohail; Goodman, Anna; Creutzig, Felix; Woodcock, James; Tainio, Marko; Holmes, Tisha; Eisenman, David; Warwick-Booth, Louise; Coan, Susan; Bagnall, Anne-Marie; et al.
CITY KNOW-HOW: Worrying trends in terms of human health and planetary health are receiving increasing global concern. City leadership, planning and development all place the constraints on urban behaviours and lifestyles, usually accelerating the problems. It is imperative that human health and environmental impacts become core foci in urban policies around the world. Changing our trajectory will require concerted action. Cities & Health aims to be part of that change; it is dedicated to supporting the flow of knowledge, in all directions, to help make this happen. We support better communication between researchers, practitioners, policy-makers, communities, and decision-makers in cities. This is the primary purpose of this City Know-how section of the journal. 'Research for city practice' disseminates lessons research, allowing researchers to explain new knowledge and key messages arising from their studies for city leaders, communities, and the professions involved in city policy and practice. 'City shorts' provide glimpses of what is being attempted or achieved 'on the ground' and 'case studies' are where you will find evaluations of interventions. Lastly, 'Commentary and debate' extends the conversations we are having to develop and mobilise important and innovative thinking. We invite you to join these conversations. In order to strengthen communities of interest, we would like to include many and varied voices, including those from practitioners, politicians and policy-makers and researchers who are supporting health and health equity in everyday urban lives. Whether you are a just starting out on your journey, or an old hand, we would love to hear from you!